Cerebral Hemodynamic Responses to the Sensory Conflict Between Visual and Rotary Vestibular Stimuli: An Analysis With a Multichannel Near-Infrared Spectroscopy (NIRS) System - Nguyen, Nghia Trong; Takakura, Hiromasa; Nishijo, Hisao; Ueda, Naoko; Ito, Shinsuke; Fujisaka, Michiro; Akaogi, Katsuichi; Shojaku, Hideo (Frontiers in Human Neuroscience, 2020)
Sensory conflict among visual, vestibular and somatosensory information induces vertiginous sensation and postural instability. To elucidate the cognitive mechanisms of the integration between the visual and vestibular cues in humans, we analyzed the cortical hemodynamic responses during sensory conflict between visual and horizontal rotatory vestibular stimulation using a multichannel near-infrared spectroscopy (NIRS) system. The subjects sat on a rotatory chair that was accelerated at 3°/sec2 for 20 sec to the right or left, kept rotating at 60°/sec for 80 sec, and then decelerated at 3°/sec2 for 20 sec. The subjects were instructed to watch white stripes projected on a screen surrounding the chair during the acceleration and deceleration periods. The white stripes moved in the two ways; in the “congruent” condition, the stripes moved in the opposite direction of chair rotation at 3°/sec2 (i.e., natural visual stimulation), whereas in the “incongruent” condition, the stripes moved in the same direction of chair rotation at 3°/sec2 (i.e., conflicted visual stimulation). The cortical hemodynamic activity was recorded from the bilateral temporoparietal regions. Statistical analyses using NIRS-SPM software indicated that hemodynamic activity increased in the bilateral temporoparietal junctions (TPJ) and human MT+ complex, including the medial temporal area (MT) and medial superior temporal area in the incongruent condition. Furthermore, subjective strength of the vertiginous sensation was negatively correlated with hemodynamic activity in the dorsal part of the supramarginal gyrus in and around the intraparietal sulcus (IPS). These results suggest that sensory conflict between the visual and vestibular stimuli promotes cortical cognitive processes in the cortical network consisting of the TPJ, the medial temporal gyrus (MTG) and IPS, which might contribute to self-motion perception to maintain a sense of balance or equilibrioception during sensory conflict.